NoSQL real-time database performance comparison. Issue 2 (4th March 2018) - Pereira, Diogo Augusto; Ourique de Morais, Wagner; Pignaton de Freitas, Edison
Abstract: The amount of data being produced is increasing constantly, as the number and variety of connected devices are growing and the advances in data storage and mining are supporting this evolution. However, storing and handling high quantities of data is challenging the current Relational Database Management Systems. Big Data and its related products came to help in this matter, and the NoSQL databases arise with the purpose to offer better solutions and features to handle massive amounts of data with higher performance, sometimes near real-time. The present study presents the NoSQL databases scenario and background, and elaborates a detailed study with the characteristics, a features comparison and a performance evaluation of three different NoSQL databases extensively used in the market nowadays: Couchbase, MongoDB and RethinkDB. Tests were performed in two different scenarios: single thread and multiple threads. The results reveal that Couchbase had a better performance at most of the operations, except for retrieving multiple documents and inserting documents with multiple threads, operations in which MongoDB scored better. Abstract : Results of the POST operation tests using a multiple threads scenario. The graphic presents the response time of each database.